A Qualitative Study of Special Education Certification Methods and How They Affect Teacher Efficacy - Green, Sean (Journal of the American Academy of Special Education Professionals, 2012)
A teacher shortage in the area of special education has led to an increase in the number of special education teachers who are teaching out-of-field. The lack of pedagogical training of these teachers creates concern about the effectiveness of these teachers. This qualitative study explores the teacher-efficacy of four special education teachers with varying backgrounds. One of the teachers was a traditionally certified special education teacher; the other teachers had received their initial certification in areas other than special education, and later became certified in special education by passing a state examination. Qualitative data demonstrated that all four had genuine concern for their students, and all four voiced belief in their ability to teach students with disabilities. However, there was a clear difference in instructional strategies used as well as their concerns about external factors, which may affect a student’s ability to learn.